Quick preparation of ABO‐incompatible living donor liver transplantation for acute liver failure. Issue 3 (17th January 2022) - Lee, Wei‐Chen; Cheng, Chih‐Hsien; Lee, Chen‐Fang; Hung, Hao‐Chien; Lee, Jin‐Chiao; Wu, Tsung‐Han; Wang, Yu‐Chao; Wu, Ting‐Jung; Chou, Hong‐Shiue; Chan, Kun‐Ming
Abstract: Acute liver failure is life‐threatening and has to be treated by liver transplantation urgently. When deceased donors or ABO‐compatible living donors are not available, ABO‐incompatible (ABO‐I) living donor liver transplantation (LDLT) becomes the only choice. How to prepare ABO‐I LDLT urgently is an unsolved issue. A quick preparation regimen was designed, which was consisted of bortezomib (3.5 mg) injection to deplete plasma cells and plasma exchange to achieve isoagglutinin titer ≤ 1: 64 just prior to liver transplantation and followed by rituximab (375 mg/m 2 ) on post‐operative day 1 to deplete B‐cells. Eight patients received this quick preparation regimen to undergo ABO‐I LDLT for acute liver failure from 2012 to 2019. They aged between 50 and 60 years. The median MELD score was 39 with a range from 35 to 48. It took 4.75 ± 1.58 days to prepare such an urgent ABO‐I LDLT. All the patients had successful liver transplantations, but one patient died of antibody‐mediated rejection at post‐operative month 6. The 3‐month, 6‐month, and 1‐year graft/patient survival were 100%, 87.5%, and 75%, respectively. In conclusion, this quick preparation regimen can reduce isoagglutinin titers quickly and make timely ABO‐I LDLT feasible for acute liver failure.